A place at the Nayarit : how a Mexican restaurant nourished a community - Molina, Natalia (University of California Press, 2022)
"In 1951, Doña Natalia Barraza opened the Nayarit, a Mexican restaurant in Echo Park, Los Angeles. With A Place at the Nayarit, historian Natalia Molina traces the life's work of her grandmother, remembered by all who knew her as Doña Natalia--a generous, reserved, and extraordinarily capable woman. Doña Natalia immigrated alone from Mexico to L.A., adopted two children, and ran a successful business. She also sponsored, housed, and employed dozens of other immigrants, encouraging them to lay claim to a city long characterized by anti-Latinx racism. Together, the employees and customers of the Nayarit maintained ties to their old homes while providing one another safety and support. The Nayarit was much more than a popular eating spot: it was an urban anchor for a robust community, a gathering space where ethnic Mexican workers and customers connected with the tastes of their patria chica, one another, and the city they now called home. Through deep research and vivid storytelling, Molina follows restaurant workers from the kitchen and the front of the house across borders and decades. Their stories illuminate the many facets of the immigrant experience, from the pressures of racism and segregation, to the complex networks of family and community, the cross-currents of gender and sexuality, and the small but essential pleasures of daily life. The Nayarit was a local landmark, popular with Hollywood stars as well as restaurant workers from across the city, and beloved for its fresh, traditionally Mexican food. But as Molina argues, it was also, and most importantly, a place where ethnic Mexicans and other Latinx L.A. residents could step into the fullness of their lives, nourishing themselves and one another. A Place at the Nayarit is a stirring exploration of how racialized minorities create a sense of belonging, and will resonate with anyone who has felt like an outsider, but had a special place where they felt like an insider"--